2013
DOI: 10.1039/c3cs60140d
|View full text |Cite
|
Sign up to set email alerts
|

A voyage into the synthesis and photophysics of homo- and heterobinuclear ensembles of phthalocyanines and porphyrins

Abstract: The remarkable properties of both phthalocyanines and porphyrins as individual building blocks have motivated the synthesis and study of homo- and heterobinuclear conjugates as light-harvesting systems. These planar chromophores share important electronic features such as high molar absorption coefficients, rich redox chemistry and interesting photoinduced energy and/or electron transfer abilities. In addition, some of these properties can be tuned by the introduction of different peripheral substituents and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 279 publications
(339 reference statements)
1
106
0
Order By: Relevance
“…In particular, depending on the chemical nature of the carbonyl (aldehyde or ketone) and amino acid derivatives, different functional groups can be introduced on the three different positions of the pyrrolidine ring, and a large variety of [60]fullerene dyads and triads can be synthesized a priori. [7,11,17,[32][33][34][35][36] By taking advantage of the versatile 1,3-dipolar cycloaddition of azomethine ylides to C 60 , [23] we found that ketones could be the precursors of choice to form tetrads. Nevertheless, only a limited number of reports describe the 1,3-dipolar cycloaddition of azomethine ylides using ketones, [37][38][39][40][41][42][43][44][45][46][47] and in most cases with modest yields (< 40 %).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, depending on the chemical nature of the carbonyl (aldehyde or ketone) and amino acid derivatives, different functional groups can be introduced on the three different positions of the pyrrolidine ring, and a large variety of [60]fullerene dyads and triads can be synthesized a priori. [7,11,17,[32][33][34][35][36] By taking advantage of the versatile 1,3-dipolar cycloaddition of azomethine ylides to C 60 , [23] we found that ketones could be the precursors of choice to form tetrads. Nevertheless, only a limited number of reports describe the 1,3-dipolar cycloaddition of azomethine ylides using ketones, [37][38][39][40][41][42][43][44][45][46][47] and in most cases with modest yields (< 40 %).…”
Section: Synthesismentioning
confidence: 99%
“…[6,7] In particular, their use in donor-acceptor systems for photovoltaic devices has impressively expanded. [8,9] To this end, a variety of [60]fullerene derivatives linked to electron-donating units such as, among others, porphyrins, [10][11][12][13][14] tetrathiafulvalenes (TTFs), [15] ferrocene, [16] phthalocyanines, [17] oligophenylenevinylenes, [18] and transition-metal complexes [19][20][21] have been prepared. The mechanisms of photoinduced electron and energy transfer have been elucidated by means of timeresolved spectroscopic methods, thus showing a strong intramolecular quenching of the excited singlet and triplet states of C 60 through the formation of charge-separated (CS) radical ion pairs.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 The triple bond is extremely important in the assembly of different nano-scale molecules, such as fullerenes, nano-tubes or porphyrins. Moreover, the triple bond moiety has been employed as a starting material for a large number of different reactions, such as click chemistry, 3 alkyne hydroamination, 4 Pd-catalyzed cross-coupling, 5 olefin metathesis, 6 and [2 + 2 + 2] cycloaddition arene formation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a wide variety of new approaches for incorporating alkyne moieties into organic molecules using metals (formation of C sp -C sp 2 or C sp -C sp 3 bonds) have appeared.…”
Section: Introductionmentioning
confidence: 99%
“…1 Their ubiquity is also related to strongly coupled electronic and geometric structures that display highly selective responsivity towards the environment. Since their physicochemical attributes are readily modulated by synthetic substitutions on the planar π-conjugated porphyrinring and by the nature of the central metal ion, 2,3 MPs constitute a versatile class of building blocks, which can be incorporated into Donor-Acceptor (D-A) assemblies. These molecular complexes provide a wide range of fullyfunctional systems for photovoltaic [4][5][6] and photocatalytic applications, 7 as well as biomimetic models for disentangling in-vivo working mechanisms.…”
Section: Introductionmentioning
confidence: 99%